Generalized partially coherent power-exponent-phase vortex beams. (December 2022) - Huang, Zewei; Yang, Yanbin; Pan, Keming; Zeng, Zishuai; Xu, Jia; Zhao, Daomu
Highlights: We propose a generalized partially coherent power-exponent-phase vortex beam. We study its generation and propagation characteristics in space-frequency domain. We summarize these characteristics by combining theory and experiment. Abstract: We propose a generalized partially coherent power-exponent-phase vortex beam, and study its generation and propagation characteristics in space-frequency domain. A complete transmission theory suitable for all generalized power-exponent-phase vortex beams is established and then demonstrated by experiments. The results show that generalized partially coherent power-exponent-phase vortex beams have their own characteristics in fan-shaped intensity distribution, intensity distribution of main lobes and side lobes and phase singularities. By combining theory and experiments, we summarize these characteristics, and put forward some potential application prospects.